Group Positive Psychotherapy to Improve Social Self-efficacy in Housewives Living with HIV - Magdalena, Cory; Hasanat, Nida Ul (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2024)
Housewives living with HIV are a vulnerable group that is often marginalized in society. This study examined the effects of group positive psychotherapy on improving the social self-efficacy of housewives living with HIV, which is essential for them to access necessary psychosocial services. Participants in this study were 7 housewives aged 28 to 37 year-old with HIV in Yogyakarta, selected using referral sampling. The quasi-experimental study employed a one-group pretest-posttest design using a double pretest. The group positive psychotherapy- called the ADAPTIF (I Can Be Positive) Program in this study, consisted of six sessions conducted twice a week. The instruments used were the Social Self-Efficacy Scale, modified from the Perceived Social Self-Efficacy Scale, and the Positive Psychotherapy Inventory (PPTI). The researcher used Wilcoxon’s signed-rank test to conduct data analysis. Results showed that Group Positive Psychotherapy significantly improved participants’ social self-efficacy (z = -2.028; p < 0.05).